A plant to plate pilot: a cold‐climate high school garden increased vegetable selection but also waste. (7th May 2015) - Wansink, Brian; Hanks, Andrew S.; Just, David R.
Abstract Aim Can high school gardens in cold climates influence vegetable intake in the absence of nutrition education? Methods This study followed a before/after design where student tray‐waste data were collected using the quarter‐waste method. The study took place March–April 2012 in a high school in upstate New York. The subjects were 370 enrolled high school students that purchased lunch from the school cafeteria. Prior to the introduction of garden greens in the salad, salads were served as usual. On April 24, harvested greens were included in the salad, and changes in selection and plate waste were measured. Results When the salad bar contained garden produce, the percentage of students selecting salad rose from 2% to 10% (p < 0.001), and on average, students ate two‐thirds of the serving they took. Although waste increased relative to the control (from 5.56% to 33.33% per serving; p = 0.007), more students were consuming at least some salad. Conclusion This preliminary investigation suggests that school gardens increased selection and intake of school‐raised produce. Although a third was not eaten, it is promising to see that still more produce was consumed compared to the past.